THE FEATURES OF COLOR SOLUTIONS OF UKRAINIAN ONLINE STORES` LOGOS - Vasyliev, O. S.; Kolosnichenko , O. V. (Art and Design, 2024)
Purpose. To select, analyze, and systematize the logos of Ukrainian online stores of various product categories to identify the characteristic features of their color solutions. Methodology. The methodological basis of the study is a comprehensive approach, methods of analytical and visual-analytical analysis of research objects, and systematization of information on the varieties of color solutions of logos of well-known Ukrainian online stores of 24 product categories. The selection of e-commerce enterprises has been carried out using search engine ratings. Results. An analysis of scientific and practical literature on the specified topic has been conducted. And the information on the psychological and associative influence of colors on consumers has been systematized. Therefore, based on the analysis of color solutions of 720 logos of Ukrainian online stores, their typical variants in different product categories have been selected and described. Also, a clear relationship between the color solution of the online store logo and the category of goods sold has been revealed. Typical color solutions of one-color logos, as well as schemes of color combinations in two-color, three-color, and multi-color logos of linguistic and mixed types of online stores of various product categories, are defined and described. The logos of online stores of certain product categories with similar color schemes were selected and combined into groups. Scientific novelty. Information on color solutions of online store logos is systematized. Typical colors and color combinations for logos of e-commerce brands of various product categories are identified. The principles of color combinations in logos of online stores of various product categories are determined. Practical significance. It is advisable to use the obtained results both in the development of logos of new e-commerce enterprises and in the redesign of existing ones. The results of the research can be used in further scientific research on the design of corporate style of sites for e-commerce enterprises.